Pengembangan Skala Kepuasan Kerja pada Karyawan Indonesia - Purwanto S.K; Rismawati Rismawati; Endah Murtiana Sari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The Short Index of Job Satisfaction (SIJS) is a measurement tool that implements a general theory of job satisfaction with a unidimensional model. This scale is used to measure job satisfaction among employees in general, with a total of five items adapted into Indonesian. The purpose of this study was to test the validity and reliability of the job satisfaction construct among employees. The research subjects were employees in the Greater Jakarta area (N=112). Confirmatory factor analysis (CFA) was used to test the construct of this instrument using MPlus7 software, and reliability testing was conducted using SPSS23 software. The results showed that there were four items in the Short Index of Job Satisfaction (SIJS) that measured job satisfaction, while one item was found not to measure job satisfaction. The reliability test yielded a Cronbach's alpha value of 0.766. These findings support the use of this general job satisfaction measurement as an acceptable tool for measuring job satisfaction. Further research could test this on other samples (e.g., more specific occupational groups), including in other countries/cultures, to evaluate the cross-cultural invariance of the SIJS.